Analysis of the Use of Social Media in Cyber Public Relations Activities of Pondok Darul Hijrah - M. Halim Saputra; Mohammad Luthfi (Jurusan Ilmu Komunikasi UTM, 2023)
Pondok Darul Hijrah Martapura uses various social media platforms in conveying various pesantren information to the community. Social media-based publicity activities are one of the applications of cyber public relations pesantren. This study aims to analyze the use of social media as an information medium for Pondok Darul Hijrah in Cyber Public Relations activities referring to Chris Heuer's 4C theory with four indicators of context, communication, collaboration, and connection. The approach used in this research is qualitative with a case study method. Data collection through observation, interviews, and documentation. Data analysis using Miles and Huberman's interactive model. The results showed that in the context indicator, the message was packaged in the form of videos and interesting content containing mahfudzot, pesantren information, student development, student teaching and learning activities. In the communication indicator, information is conveyed through social media platforms Instagram, Youtube and Facebook by providing quick feedback on each follower's questions. Indicator collaboration is carried out by making votes on instastory about student activities, captions recommending likes, comments, and shares, posting student achievements and connection indicators through rapid dissemination of information about pesantren activities by providing information regularly every day. Research provides benefits in the development of communication scientific studies, especially in the application of cyber public relations pesantren.